2020
DOI: 10.3389/fgene.2020.00372
|View full text |Cite
|
Sign up to set email alerts
|

Disease Severity-Associated Gene Expression in Canine Myxomatous Mitral Valve Disease Is Dominated by TGFβ Signaling

Abstract: Myxomatous mitral valve disease (MMVD) is the most common acquired canine cardiovascular disease and shares many similarities with human mitral valvulopathies. While transcriptomic datasets are available for the end-stage disease in both species, there is no information on how gene expression changes as the disease progresses, such that it cannot be stated with certainty if the changes seen in end-stage disease are casual or consequential. In contrast to humans, the disease in dogs can be more readily examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 47 publications
2
35
0
1
Order By: Relevance
“…We have recently shown that the transcriptome of the mitral valve changes as MMVD advances from the normal valve to the severely diseased Whitney grade 4 valve [21]. We found that TGFβ was the dominant signalling pathway controlling pathogenesis, consistent with ndings in cultured valve interstitial cells [22].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We have recently shown that the transcriptome of the mitral valve changes as MMVD advances from the normal valve to the severely diseased Whitney grade 4 valve [21]. We found that TGFβ was the dominant signalling pathway controlling pathogenesis, consistent with ndings in cultured valve interstitial cells [22].…”
Section: Discussionsupporting
confidence: 83%
“…There were clear similarities in gene enrichment analysis and GO terms comparing both diseased groups to normal, including genes recognised as hallmarks of canine MMVD, such as ACTA2 (encoding α-SMA) and HTR2B (encoding 5HT2B receptor) [18,27]. This likely re ects the global gene signature typical of MMVD where there is aberrant extra-cellular matrix remodelling as a consequence of changes in TGFβ signalling [18,19,21,36]. The other shared DEGs, in particular those coding for the myosin heavy chains and growth factors, suggest the involvement of TGFβ non-canonical signalling pathways affecting downstream signals including MEK, ERK1/2, IP3 and RhoGTPase [37].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, there is evidence of enhanced 5HT signalling in both human and canine MMVD valve tissue and valve interstitial cells (VIC) exposed to tensile strain, and genetic variation in the exons of the 5HT transporter gene ( SLC6A4 , also known as SERT ) may be associated with MMVD development in the Maltese terrier [ 16 , 17 ]. Changes in expression of the 5HT receptor gene are reported for the canine mitral valve transcriptome, and in the dog HTR2B expression is associated with disease progression [ 18 21 ]. However, 5HT does not induce disease phenotype in cultured VICs and expression of 5HT receptor genes is controlled by TGFβ1 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with MVP have a risk of cardiovascular morbidity and mortality similar to that of the general population, though moderate to severe MR and left ventricular ejection fraction less than 50% have been postulated to increase the risk of adverse cardiac events. Other risk factors for cardiovascular morbidity include flail mitral leaflet, left atrium size greater than 40 mm, atrial fibrillation, and age above 50 years [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%